About the sterilization of chitosan hydrogel nanoparticles - Galante, Raquel (2017)
In the last years, nanostructured biomaterials have raised a great interest as platforms for delivery of drugs, genes, imaging agents and for tissue engineering applications. In particular, hydrogel nanoparticles (HNP) associate the distinctive features of hydrogels (high water uptake capacity, biocompatibility) with the advantages of being possible to tailor its physicochemical properties at nano-scale to increase solubility, immunocompatibility and cellular uptake. In order to be safe, HNP for biomedical applications, such as injectable or ophthalmic formulations, must be sterile. Literature is very scarce with respect to sterilization effects on nanostructured systems, and even more in what concerns HNP. This work aims to evaluate the effect and effectiveness of different sterilization methods on chitosan (CS) hydrogel nanoparticles. In addition to conventional methods (steam autoclave and gamma irradiation), a recent ozone-based method of sterilization was also tested. A model chitosan-tripolyphosphate (TPP) hydrogel nanoparticles (CS-HNP), with a broad spectrum of possible applications was produced and sterilized in the absence and in the presence of protective sugars (glucose and mannitol). Properties like size, zeta potential, absorbance, morphology, chemical structure and cytotoxicity were evaluated. It was found that the CS-HNP degrade by autoclaving and that sugars have no protective effect. Concerning gamma irradiation, the formation of agglomerates was observed, compromising the suspension stability. However, the nanoparticles resistance increases considerably in the presence of the sugars. Ozone sterilization did not lead to significant physical adverse effects, however, slight toxicity signs were observed, contrarily to gamma irradiation where no detectable changes on cells were found. Ozonation in the presence of sugars avoided cytotoxicity. Nevertheless, some chemical alterations were observed in the nanoparticles.